Bibliometric analysis and thematic review of Candida pathogenesis: fundamental omics to applications as potential antifungal drugs and vaccines - Lim, Si Jie; Muhd Noor, Noor Dina; Sabri, Suriana; Mohamad Ali, Mohd Shukuri; Salleh, Abu Bakar; Oslan, Siti Nurbaya (Oxford University Press, 2023)
Invasive candidiasis caused by the pathogenic Candida yeast species has resulted in elevating global mortality. The pathogenicity of Candida spp. is not only originated from its primary invasive yeast-to-hyphal transition; virulence factors (transcription factors, adhesins, invasins, and enzymes), biofilm, antifungal drug resistance, stress tolerance, and metabolic adaptation have also contributed to a greater clinical burden. However, the current research theme in fungal pathogenicity could hardly be delineated with the increasing research output. Therefore, our study analyzed the research trends in Candida pathogenesis over the past 37 years via a bibliometric approach against the Scopus and Web of Science databases. Based on the 3993 unique documents retrieved, significant international collaborations among researchers were observed, especially between Germany (Bernhard Hube) and the UK (Julian Naglik) whose focuses are on Candida proteinases, adhesins, and Candidalysin. The prominent researchers (Neils Gow, Alistair Brown and Frank Odds) at the University of Exeter and University of Aberdeen (second top performing affiliation), UK contribute significantly to the mechanisms of Candida adaptation, tolerance, and stress response. However, the science mapping of co-citation analysis performed herein could not identify a hub representative of subsequent work since the clusters were semi-redundant. The co-word analysis that was otherwise adopted, revealed three research clusters; the cluster-based thematic analyses indicated the severeness of Candida biofilm and antifungal resistance as well as the elevating trend on molecular mechanism elucidation for drug screening and repurposing. Importantly, the in vivo pathogen adaptation and interactions with hosts are crucial for potential vaccine development.